154k views
1 vote
Find the sum of 4x^3+2x^2-4x+3 and 7x^3-4x^2+7x+8

2 Answers

3 votes

Answer: 3a^3 + 4a^2 - a + 5

Explanation:

1. (4x^3 + 2x^2 - 4x + 3) + (7x^3 - 4x^2 + 7x + 8)

combine terms with same exponent;

(4x^3 + 7x^3) + (2x^2 - 4x^2) + (-4x + 7x) + (3 +8)

= 11x^3 + (-2x^2) + 3x + 11

= 11x^3 - 2x^2 + 3x +11.............final answer

2. 3a^3 + 8a - 6 and 4a^2 -9a +11

combine terms with same exponent;

3a^3 + 4a^2 + (8a - 9a) + (-6 + 11)

= 3a^3 + 4a^2 + (-a) + 5

= 3a^3 + 4a^2 - a + 5...........final answer

User Amirreza Noori
by
4.2k points
7 votes

The sum means addition.

Add the like terms together.

4x^3+2x^2-4x+3

+ 7x^3-4x^2+7x+8

4x^3 + 7x^3 = 11x^3

2x^2 + -4x^2 = -2x^2

-4x +7x = 3x

3 +8 = 11

The answer is : 11x^3 - 2x^2 + 3x + 11

User Woot
by
4.9k points